Rh-I-UEA-1 Polymerized Liposomes Target and Image Adenomatous Polyps in the Mouse Using Optical Colonography - Celeste A. Roney; Biying Xu; Jianwu Xie; Shuai Yuan; Jeremiah Wierwille; Chao-Wei Chen; Yu Chen; Gary L. Griffiths; Ronald M. Summers (Molecular Imaging)
Mutated adenomatous polyposis coli ( APC ) genes predispose transformations to neoplasia, progressing to colorectal carcinoma. Early detection facilitates clinical management and therapy. Novel lectin-mediated polymerized targeted liposomes (Rh-I-UEA-1), with polyp specificity and incorporated imaging agents were fabricated to locate and image adenomatous polyps in APC Min /+ mice. The biomarker α- l -fucose covalently joins the liposomal conjugated lectin Ulex europaeus agglutinin (UEA-1), via glycosidic linkage to the polyp mucin layer. Multispectral optical imaging (MSI) corroborated a global perspective of specific binding (rhodamine B 532 nm emission, 590–620 nm excitation) of targeted Rh-I-UEA-1 polymerized liposomes to polyps with 1.4-fold labeling efficiency. High-resolution coregistered optical coherence tomography (OCT) and fluorescence molecular imaging (FMI) reveal the spatial correlation of contrast distribution and tissue morphology. Freshly excised APC Min bowels were incubated with targeted liposomes (UEA-1 lectin), control liposomes (no lectin), or iohexol (Omnipaque) and imaged by the three techniques. Computed tomographic quantitative analyses did not confirm that targeted liposomes more strongly bound polyps than nontargeted liposomes or iohexol (Omnipaque) alone. OCT, with anatomic depth capabilities, along with the coregistered FMI, substantiated Rh-I-UEA-1 liposome binding along the mucinous polyp surface. UEA-1 lectin denotes α- l -fucose biomarker carbohydrate expression at the mucin glycoprotein layer; Rh-I-UEA-1 polymerized liposomes target and image adenomatous polyps in APC Min mice.